First results of the use of a continuously flowing lithium limiter in high performance discharges in the EAST device. (16th March 2016) - Hu, J.S.; Zuo, G.Z.; Ren, J.; Yang, Q.X.; Chen, Z.X.; Xu, H.; Zakharov, L.E.; Maingi, R.; Gentile, C.; Meng, X.C.; Sun, Z.; Xu, W.; et al.
Abstract: As an alternative choice of solid plasma facing components (PFCs), flowing liquid lithium can serve as a limiter or divertor PFC and offers a self-healing surface with acceptable heat removal and good impurity control. Such a system could improve plasma performance, and therefore be attractive for future fusion devices. Recently, a continuously flowing liquid lithium (FLiLi) limiter has been successfully designed and tested in the EAST superconducting tokamak. A circulating lithium layer with a thickness of <0.1 mm and a flow rate 2 cm 3 s −1 was achieved. A novel in-vessel electro-magnetic pump, working with the toroidal magnetic field of the EAST device, was reliable to control the lithium flow speed. The flowing liquid limiter was found to be fully compatible with various plasma scenarios, including high confinement mode plasmas heated by lower hybrid waves or by neutral beam injection. It was also found that the controllable lithium emission from the limiter was beneficial for the reduction of recycling and impurities, for the reduction of divertor heat flux, and in certain cases, for the improvement of plasma stored energy, which bodes well application for the use of flowing liquid lithium PFCs in future fusion devices.